Reactivity of Single Transition Metal Atoms on a Hydroxylated Amorphous Silica Surface: A Periodic Conceptual DFT Investigation. Issue 19 (4th March 2021) - Deraet, Xavier; Turek, Jan; Alonso, Mercedes; Tielens, Frederik; Cottenier, Stefaan; Ayers, Paul W.; Weckhuysen, Bert M.; De Proft, Frank
Abstract: The drive to develop maximal atom‐efficient catalysts coupled to the continuous striving for more sustainable reactions has led to an ever‐increasing interest in single‐atom catalysis. Based on a periodic conceptual density functional theory (cDFT) approach, fundamental insights into the reactivity and adsorption of single late transition metal atoms supported on a fully hydroxylated amorphous silica surface have been acquired. In particular, this investigation revealed that the influence of van der Waals dispersion forces is especially significant for a silver (98 %) or gold (78 %) atom, whereas the oxophilicity of the Group 8–10 transition metals plays a major role in the interaction strength of these atoms on the irreducible SiO2 support. The adsorption energies for the less‐electronegative row 4 elements (Fe, Co, Ni) ranged from −1.40 to −1.92 eV, whereas for the heavier row 5 and 6 metals, with the exception of Pd, these values are between −2.20 and −2.92 eV. The deviating behavior of Pd can be attributed to a fully filled d‐shell and, hence, the absence of the hybridization effects. Through a systematic analysis of cDFT descriptors determined by using three different theoretical schemes, the Fermi weighted density of states approach was identified as the most suitable for describing the reactivity of the studied systems. The main advantage of this scheme is the fact that it is not influenced by fictitious Coulomb interactions between successive, charged reciprocal cells. Moreover, the contribution of the energy levels to the reactivity is simultaneously scaled based on their position relative to the Fermi level. Finally, the obtained Fermi weighted density of states reactivity trends show a good agreement with the chemical characteristics of the investigated metal atoms as well as the experimental data. Abstract : SAC reactivity from theory : A periodic conceptual DFT investigation elucidating the nature of the adsorption and catalytic activity of single silica‐supported late transition metal atoms was undertaken revealing the evidence of a strong correlation with experimental data and chemical properties.